Edukasi Pencegahan Anemia Pada Remaja di SMA Muhammadiyah 2 Bandar Lampung - Syaadatun Nadiah; Anjar Hermadi Saputro; Sarmoko Sarmoko; Nur Adliani; Tantri Liris Nareswari; Nisa Yulianti Suprahman; Ahmad Bayu Satriawan; Reny Haryani; Annisa Nofriani; Sudewi Mukaromah Khoirunnisa (I-Com: Indonesian Community Journal, 2025)
Anemia is one of the health problems that can occur in adolescents and high school students. According to data from the Ministry of Health, many adolescents in Indonesia still suffer from anemia, as indicated by the still quite high prevalence of anemia. This activity aims to foster and increase awareness among adolescents and students about the importance of understanding the causes and impacts of anemia in adolescents. The implementation of this community service consists of several stages, namely the planning, implementation and evaluation stages, as well as follow-up carried out through pre-tests and post-tests to evaluate the results of the education that has been carried out. Based on the evaluation results, the majority of students showed increased awareness of the importance of a nutritious diet and a healthy lifestyle in preventing anemia. Interactive discussions also showed students' enthusiasm in understanding the impact of anemia on health and learning productivity.